1991
DOI: 10.1099/00222615-35-4-219
|View full text |Cite
|
Sign up to set email alerts
|

An Indian hospital study of viral causes of acute respiratory infection in children

Abstract: Summary. From Sept. 1986 to Jan. 1989, a hospital-based study was conducted on 736 children, under 5 years of age, with acute respiratory infection. Nasopharyngeal secretions were examined for viruses by culture and by immunofluorescence. Viruses were detected in 22% of specimens : respiratory syncytial(5%), parainfluenza (5%), influenza A (4%), influenza B (273, adenovirus (373, measles (3%). The highest rates of detection were with patients diagnosed clinically as pneumonia or upper respiratory tract infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…Total case positivity of 37.1% was within the range of 22.0 to 51.9% as reported earlier from other countries 10 and India. 6,[11][12][13][14][15] A three-year systematic study conducted at Vellore (Southern India) indicated viral etiology in 49% and 38% of lower and upper respiratory tract infection cases, respectively. 2 A recent study by Legg et al 16 to understand the viral etiology of respiratory infection in infants during their first winter indicated 46% positivity for picornaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Total case positivity of 37.1% was within the range of 22.0 to 51.9% as reported earlier from other countries 10 and India. 6,[11][12][13][14][15] A three-year systematic study conducted at Vellore (Southern India) indicated viral etiology in 49% and 38% of lower and upper respiratory tract infection cases, respectively. 2 A recent study by Legg et al 16 to understand the viral etiology of respiratory infection in infants during their first winter indicated 46% positivity for picornaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified RSV in 29 of 67 (43.3%) children with clinically defined pneumonia, although the age range was not restricted to under-five children [37]. A hospital-based study [38] applied viral culture and immunofluorescence techniques in 736 children <5 years of age with ARI (pneumonia 39%, upper respiratory infection 38%, croup or bronchiolitis 23%). Among those with pneumonia, viruses were detected in 66 of 287 (23%) cases.…”
Section: Etiology Of Childhood Pneumonia In Indiamentioning
confidence: 98%
“…Viruses are a frequent cause of upper respiratory tract infections in children (Chew et al, 1998;de Arruda et al, 1991;Jain et al, 1991;Sutomöller et al, 1995;Winter et al, 1996). Most surveillance studies of respiratory viral infections were conducted in developed countries (Fox et al, 1966(Fox et al, , 1972Lina et al, 1996;Tumova et al, 1988).…”
Section: Introductionmentioning
confidence: 97%